2017
DOI: 10.1186/s12951-016-0238-1
|View full text |Cite
|
Sign up to set email alerts
|

Poly-lactic acid nanoparticles (PLA-NP) promote physiological modifications in lung epithelial cells and are internalized by clathrin-coated pits and lipid rafts

Abstract: BackgroundPoly-lactic acid nanoparticles (PLA-NP) are a type of polymeric NP, frequently used as nanomedicines, which have advantages over metallic NP such as the ability to maintain therapeutic drug levels for sustained periods of time. Despite PLA-NP being considered biocompatible, data concerning alterations in cellular physiology are scarce.MethodsWe conducted an extensive evaluation of PLA-NP biocompatibility in human lung epithelial A549 cells using high throughput screening and more complex methodologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 78 publications
1
34
0
Order By: Relevance
“…Cells were seeded in a 6-well plate (3×10 5 /well) using complete DMEM and allowed to attach overnight. Media was replaced with DMEM containing 5% FBS plus enoxaparin and doxorubicin alone or combined and incubated for 24 h. Staurosporine (STS, 4 μM), a commonly used protein kinase inhibitor and activator of apoptosis, was used as positive control (30,31). STS was dissolved in DMSO and diluted to the final concentration (4 μM) to contain 0.4% DMSO.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were seeded in a 6-well plate (3×10 5 /well) using complete DMEM and allowed to attach overnight. Media was replaced with DMEM containing 5% FBS plus enoxaparin and doxorubicin alone or combined and incubated for 24 h. Staurosporine (STS, 4 μM), a commonly used protein kinase inhibitor and activator of apoptosis, was used as positive control (30,31). STS was dissolved in DMSO and diluted to the final concentration (4 μM) to contain 0.4% DMSO.…”
Section: Methodsmentioning
confidence: 99%
“…Endocytosis can be further divided into macropinocytosis, clathrin-mediated endocytosis, caveolin-mediated endocytosis, and clathrin-/caveolin-independent endocytosis [19]. It is widely accepted that most nanoscaled objects are transported across the lipid bilayer through clathrin-mediated endocytosis [20][21][22], which is highly dependent upon the fluidity of the cell membrane [23]. Although the influence of nanomaterials has been extensively studied, the influence of stem cells, especially with respect to passaging, has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal tract is the primary physiological barrier for the oral absorption of multiple substances [ 28 , 29 ]. Lehr et al [ 30 , 31 ] reported that in the inflamed colon, an increased adherence of particles was observed in the thicker mucus layer. A size dependency of the deposition was found, with an increased number of attached particles to the colon found compared with the control group.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that clathrin-mediated endocytosis was an uptake process, which occurs through the formation of clathrin-coated vesicles that form from the plasma membrane [ 26 ]. Clathrin-mediated endocytosis was involved primarily in the internalization of receptors [ 31 , 35 , 36 ]. However, under inflammatory conditions, there are changes in protein complexes consisting of transmembrane proteins that interact in the extracellular environment with adjacent cells and in the intracellular environment with adaptor proteins that link to the cytoskeleton.…”
Section: Resultsmentioning
confidence: 99%